Health Financing in Indonesia A Reform Road Map - Claudia Rokx, Claudia Rokx George Schieber Pandu Harimurti Ajay Tandon Aparnaa Somanathan (The World Bank, 2009)
nd macroeconomic environments. This study, based on both the Indonesia-specific and global evidence bases, provides a critically needed road map for the reform effort. Its analytical assessment of the current Indonesian health system and its strengths and weaknesses provides the health policy baseline for the reform. The assessment of key policy parameters needing resolution and of plausible transition options based on the goals of maximizing health outcomes, financial protection, and consumer responsiveness provides the government with an extremely valuable guide for moving the reform forward. The study also provides useful inputs to Indonesia’s next Five-Year Development Plan. As such, this study is an invaluable tool for assisting the government at this critical juncture in its reform process.nd macroeconomic environments. This study, based on both the Indonesia-specific and global evidence bases, provides a critically needed road map for the reform effort. Its analytical assessment of the current Indonesian health system and its strengths and weaknesses provides the health policy baseline for the reform. The assessment of key policy parameters needing resolution and of plausible transition options based on the goals of maximizing health outcomes, financial protection, and consumer responsiveness provides the government with an extremely valuable guide for moving the reform forward. The study also provides useful inputs to Indonesia’s next Five-Year Development Plan. As such, this study is an invaluable tool for assisting the government at this critical juncture in its reform process.